ANALISIS KELAYAKAN DAN PERSPEKTIF PENGEMBANGAN PENGOLAHAN SAGU DI SULAWESI TENGGARA - Zainal Abidin; Bungati -; Musadar - (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2019)
Feasibility and Perspective Analysis of Sagu Processing Development in South Sulawesi. Sago starch has an important role both as a staple food and a material for making various other processed food products. Sago processing can produce both wet sago and dried sago starch. The study was conducted to determine the feasibility of the sago processing business and its development perspective in Southeast Sulawesi. The study was conducted in South Konawe District in March - December 2017. Data were collected through field observations of the Biosagu Sejahtera Farmer Group in Matalamokula Village, North Moramo Sub District which has wet and dry sago production units. The data collected were the production capacity of wet sago and dry sago, the price of sago trees, the price of wet sago and dry sago, the production costs include labor costs, fuel costs, packaging costs as well as the costs of depreciation of tools and machinery. Data were analyzed using a profit equation. The results showed that the production of wet sago starch on a processing scale of 12 sago trees (1 production cycle) was feasible because it provided a profit of 7,314,000 IDR with Production-Break Even Point (PBEP) of 2,359 kg and Price BEP of 1,493 IDR and RCR value was 1.93. Likewise, dry sago production business was feasible with an RCR of 2.18; BEP from the production and price were 460 kg and 7,571 IDR respectively and provided profit of around 6,435,000 IDR. Thus the production of wet sago and dry sago can be alternative non-farm employment in rural areas. Perspective of sago processing in Southeast Sulawesi in the future is quite good due to the several supports such as availability of sago plantation area, the availability of human resources, the technology available as well as policies and regulations from the government. The demand for sago in the future will be influenced by the demand to substitute commodities that are still imported such as wheat and sugar as well as products that have a large domestic use, namely bioethanol. The development of sago in the future needs to respond to changes in demand by changing the management model with conventional management to modern technology. Tepung sagu memiliki peran penting baik sebagai bahan pangan pokok maupun sebagai bahan pembuatan berbagai produk olahan pangan lainnya. Pengolahan sagu dapat menghasilkan tepung sagu basah dan tepung sagu kering. Kajian dilakukan untuk mengetahui kelayakan usaha pengolahan sagu serta perspektif pengembangannya di Sulawesi Tenggara. Penelitian dilakukan di Kabupaten Konawe Selatan bulan Maret – Desember tahun 2017. Pengumpulan data dilakukan melalui observasi lapangan terhadap Kelompok Tani Biosagu Sejahtera Desa Matalamokula, Kecamatan Moramo Utara yang memiliki unit produksi sagu basah dan unit produksi sagu kering. Data yang dikumpulkan adalah kapasitas produksi sagu basah dan sagu kering, harga pohon sagu, harga sagu basah dan sagu kering, biaya produksi meliputi biaya tenaga kerja, biaya bahan bakar, biaya kemasan serta biaya penyusutan alat dan mesin, analisis data dilakukan menggunakan persamaan keuntungan. Hasil penelitian menunjukkan bahwa usaha produksi tepung sagu basah pada skala pengolahan 12 pohon sagu (1 siklus produksi) layak diusahakan karena memberikan keuntungan sebesar Rp 7.314.000, dengan nilai Titik Impas Produksi (TIP) dan Titik Impas Harga (TIH) masing-masing 2.359 kg dan Rp 1.493 serta nilai RCR sebesar 1,93. Usaha produksi sagu kering layak dilakukan dengan nilai RCR sebesar 2,18; nilai TIP dan TIH masing-masing 460 kg dan Rp 7.571 serta memberikan keuntungan sebesar Rp 6.435.000. Usaha produksi sagu basah maupun sagu kering dapat menjadi alternatif lapangan kerja non farm di pedesaan. Perspektif pengolahan sagu di Sulawesi Tenggara ke depan cukup baik karena ditunjang ketersediaan areal pertanaman sagu cukup luas, ketersediaan sumberdaya manusia, teknologi hingga dukungan kebijakan dan regulasi. Permintaan sagu ke depan akan dihela oleh permintaan untuk mensubstitusi komoditas-komoditas yang selama ini masih diimpor seperti gandum dan gula maupun produk yang pemanfaatannya dalam negeri cukup besar yaitu bioetanol. Pengembangan sagu juga perlu merespon perubahan-perubahan permintaan tersebut dengan mengubah model pengelolaan dengan teknologi konvensional menjadi teknologi modern.